Space chimps (Hollywood, CA : Brash Entertainment, 2008)
"You are Ham III, and it is up to you and your space chimp crew to free the imprisoned aliens of the planet Malgor. You must use your problem solving brains and acrobatic brawn to survive thick alien jungles, escape dry desolate canyons and well guarded dungeons in order to defeat the evil Zartog and find your way home"--Container.
Title and edition statement from disc surface.
1-2 players ; live online enabled.
System requirements: Xbox 360 ; 64 KB to save game.
Keywords: Chimpanzees; Astronauts; Outer space -- Exploration; Computer adventure games; Video games; Computer adventure games; Video games